2008
DOI: 10.1901/jaba.2008.41-83
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive and Experimental Analyses of Potential Precursors to Problem Behavior

Abstract: descriptive assessment, functional analysis, lag-sequential analysis, precursors, problem behavior, response-class hierarchies

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
91
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(96 citation statements)
references
References 15 publications
2
91
2
1
Order By: Relevance
“…Further, the current study extends Borrero and Borrero (2008) by conducting comparative probability analyses with multiple potential precursor responses to determine to what extent findings obtained from the indirect assessment matched those from the descriptive assessment. The present findings also replicate previous research showing that outcomes of the functional analysis of both the target behavior and precursor behavior showed the same outcome, and the functional analysis of precursor behavior resulted in fewer occurrences of the target response.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Further, the current study extends Borrero and Borrero (2008) by conducting comparative probability analyses with multiple potential precursor responses to determine to what extent findings obtained from the indirect assessment matched those from the descriptive assessment. The present findings also replicate previous research showing that outcomes of the functional analysis of both the target behavior and precursor behavior showed the same outcome, and the functional analysis of precursor behavior resulted in fewer occurrences of the target response.…”
Section: Resultsmentioning
confidence: 87%
“…In a related study, Borrero and Borrero (2008) evaluated the utility of comparative probability analyses of descriptive assessment data for confirming the predictive relation between a hypothesized precursor response (vocalizations) and the target behavior (aggression and property destruction). Although this study demonstrated the utility of direct observation for confirming this predictive relation, the authors did not evaluate the utility of this approach for differentiating among several potential precursor responses.…”
mentioning
confidence: 99%
“…In isolation, the probability of some event (e.g., attention) is not particularly informative. When compared to the probability of the same event, given a target behavior, the unconditional probability values become more informative (Borrero & Borrero, 2008;Borrero et al, 2010;Vollmer et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Following the descriptive assessment, the data were analyzed for all caregiver-fed meals to calculate the conditional probabilities of caregiver responses following IMB, using methods described by Borrero et al (2010) and similar to those described by previous researchers (Borrero & Borrero, 2008;Vollmer et al, 2001). Conditional probabilities were analyzed using Instant Analyzer ® with an interval size of 5 s, meaning that for each occurrence of child behavior, the Instant Analyzer ® program lagged forward 5 s in the raw data to determine if a specific occurrence of caregiver behavior occurred.…”
Section: Conditional Probability Analysis (Descriptive Assessment)mentioning
confidence: 99%
“…Enquanto recurso metodológico, a avaliação funcional descritiva objetiva, mediante a obtenção de dados sobre eventos antecedentes e subsequentes aos repertórios selecionados, fornecer evidências que possam subsidiar hipóteses sobre possíveis funções operantes destes repertórios. Assim, dados derivados da execução de avaliações funcionais não autorizam ou permitem conclusões definitivas sobre relações funcionais (Bijou, Peterson & Ault, 1968;Borrero & Borrero, 2008;Lerman & Iwata, 1993;Mace e cols., 1991;Sturmey, 1996). Lerman e Iwata (1993) descreveram três tipos de avaliações funcionais descritivas.…”
unclassified